The Frequency of Different Contraceptives Uses and Their Side Effects in Clients Visiting Family Planning Center, BVH Bahawalpur (Medical Forum Monthly, 2024)
Objective: The aim of present study was to determine the frequency of different contraceptive methods and their side effects in clients visiting Family Planning Centre, BVH Bahawalpur.Study Design: Cross-sectional descriptive epidemiological studyPlace and Duration of Study: This study was conducted at Family Planning Centre; BVH Bahawalpur From 5th May 2016 to 20th June 2016.Materials and Methods: Data was collected through a pre-designed Performa after informal consent. It included questions about fertility history, use of contraceptives, their source of information and their side effects. The questionnaire was first translated into Urdu and then reverse translated in English and then filled by interviewing each client. Data was entered and analyzed by using SPSS 13.All results were presented in Frequencies ,percentages and in the form of tables and figures.Results: The most commonly practiced contraceptive methods in females were 36% hormonal injections and 29% oral pills while in males 75% condoms. The side effects, like menstrual irregularities and leucorrhoea of different contraceptive methods, were 38% with hormonal injectables, 35% with oral pills and 25% with IUCDs. No side effects were found in cases of condoms and vasectomy use.Conclusion: Out of 80 users of female contraception, 29% developed side effects like menstrual irregularities and leucorrhoea. No side effects were found in cases of condoms and vasectomy use.